2003
DOI: 10.1159/000071214
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Withdrawal Changes Cardiovascular Responses to Propranolol Challenge

Abstract: The cardiovascular effects and plasma concentrations of a single dose of propranolol (80 mg) were studied non-invasively in alcohol-dependent subjects during alcohol withdrawal (AW) on day 1 and after resolution of withdrawal symptoms on day 10. At the onset of AW, propranolol caused a bradycardic effect which was significantly weakened on day 10. This might result from an increased bioavailability of propranolol on day 1 and from marked sympathetic activity. Propranolol also produced a negative inotropic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…This study confirmed recent findings of Kähkönen (2003) in which the bradycardiac effect of propranolol weakened toward the end of WS. However, in the same study, the effects of propranolol on the negative inotropic effect were opposite: a relatively weaker effect was observed at the beginning of WS.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study confirmed recent findings of Kähkönen (2003) in which the bradycardiac effect of propranolol weakened toward the end of WS. However, in the same study, the effects of propranolol on the negative inotropic effect were opposite: a relatively weaker effect was observed at the beginning of WS.…”
Section: Discussionsupporting
confidence: 92%
“…Total concentrations of propranolol were higher during withdrawal than after resolution of the withdrawal symptoms (Kähkönen, 2003), but concentrations of unbound fraction of propranolol were opposite (Sandor et al, 1983).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…AW-related changes in adrenergic function have been shown to modulate cardiovascular responses in AW [9]. The hormones of the hypothalamus-hypophysis-adrenalaxis may also play a role.…”
Section: Introductionmentioning
confidence: 99%